Cytokine Status of Patients with Chronic Viral Hepatitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study of immunological aspects of the course of chronic viral hepatitis is relevant. The problem of chronic viral hepatitis for many states and its medical and social significance is currently increasing. Early diagnosis and prevention of complications of chronic viral hepatitis can reduce morbidity and disability.The author has developed recommendations for the early diagnosis and prognosis of complications of chronic viral hepatitis, taking into account the immune status, which contribute to improving the quality of preventive care for infectious diseases, therapists, followed by a decrease in morbidity and disability.